What has been the tax competition experience of the last 20 years? - Rachel Griffith; Alexander Klemm (Institute for Fiscal Studies (IFS), 2004)
This paper describes tax reforms in OECD countries over the last 20 years and how they are related to tax competition. Both individual countries' reforms and multilateral initiatives and developments are covered. This is followed by an overview of the empirical evidence on tax competition. Our conclusion is that the evidence for some interdependence in tax setting behaviour is strong, although the exact process driving this remains unclear. While the most basic tax competition models fail to explain the development in OECD countries, there is more than one possible explanation for the reforms undertaken if more advanced models are considered. The multilateral initiatives that were implemented however do not seem to be related to resource-based tax competition, instead they are about taxing rights.
Keywords: H25; 330; Corporation; tax; Steuerwettbewerb; Steuerreform; OECD-Staaten